The association of fibrocystic breast disease with endometrial histopathological results in abnormal uterine bleeding: Endometrial pathology in fibrocystic breast disease - Vural, Selahattin; Özdemir, Oğuz; Sağır, Meryem; Soysal, Çağanay; Yılmaz, Zehra (Journal of Surgery and Medicine, 2022)
Background/Aim: Fibrocystic breast disease (FBD) is the most frequent benign breast disease. Increased estrogen and decreased progesterone concentrations are thought to be involved in the pathogenesis of FBD. But there is insufficient data on benign breast disease and endometrial pathology. This study evaluates the association between FBD and endometrial pathology in women complaining of abnormal uterine bleeding. Methods: This study was designed as a retrospective case-control study. The medical records of women who had endometrial sampling for abnormal uterine bleeding between 2018 and 2020 were evaluated. Patients with FBD were included in the study group, while the first patients who had endometrial sampling after patients with FBD and without breast disease were recruited as the control group. Demographic, laboratory data, and endometrial histopathological results were obtained from hospital records and compared between the groups. Results: In total, 250 women (106 women with FBD and 144 without breast disease) were recruited for the study. There was no statistically significant difference in mean age, gravidity, parity, and BMI between FBD and control groups. Endometrial hyperplasia without atypia (19.8% versus 10.5%, respectively, P = 0.037) and endometrial polyp (12.2% versus 4.8%, respectively, P = 0.033) were found to be significantly increased in patients with FBD than women without the disease. There was no statistically significant difference in terms of other histopathological results between the groups. Conclusion: Evaluation of the endometrium for abnormal uterine bleeding is essential for early diagnosis and treatment of endometrial pathology, especially for endometrial cancer. In this study, we found that women with FBD have an increased risk for endometrial hyperplasia and endometrial polyp. As endometrial hyperplasia is a precursor lesion for endometrial cancer, clinicians should pay attention to and investigate menstrual bleeding abnormalities of women with FBD and should not delay the evaluation of the endometrium.